TANGGUNG JAWAB BANK X TERHADAP KERUGIAN NASABAH M-BANKING AKIBAT TRANSAKSI PIHAK TIDAK BERWENANG BERDASARKAN PERATURAN PERBANKAN: X Bank’s Responsibility For M-Banking Customer Losses Due To Unauthorized Party Transaction - Badzlin, Nadhifah Zahra Ghaisani; Purnamasari, Dian (AMICUS CURIAE, 2024)
X Bank, a foreign owned private bank operating in Indonesia since May 15, 1959, has embraced technology in its business operations in response to advancements in the digital era. This practice aims to enhance convenience and efficiency in service provided to its customers, including through m-banking service. However, issues may arise in the practice, such as a case of a customer whose funds are lost due to transactions through the X Bank’s m-banking service. The main problem is X Bank’s responsibility towards the loss suffered by Customer Y, a user of X Bank’s mobile banking platform, that was resulted from transaction transfers through the X Bank’s m-banking application. Based on research, it was found that X Bank’s internal regulations hadn’t aligned with banking related regulations. X Bank is not liable for the loss experienced by Customer Y, and no sanctions are imposed on X Bank by The Financial Services Authority as a result of the discrepancy that led to the loss suffered by Customer Y.